The influence of varying ratios of potassium, calcium and magnesium nutrition on quality and storage of potatoes (Solanum tuberosum L.) - Bester, Gabriel Gerhardus (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhDAgric)--Stellenbosch University, 1993.